Toxic effects of subchronic T-2 toxin exposure on systemic immune deficiency in developing juvenile rats - Fanshuang Meng; Junfeng Zhou; Hongyu Wang; Qingwen Li; Ning Zou (Ecotoxicology and Environmental Safety, 2025)
T-2 toxin, a potent immunosuppressive mycotoxin produced by Fusarium species, has not yet been fully elucidated regarding its immunotoxic effects under chronic exposure during developmental stages. To address the limitations of previous studies that primarily focused on single-organ assessments or acute toxicity evaluations in adult animals, this study established a 28-day subchronic T-2 toxin exposure model in Wistar juvenile rats (0–0.8 mg/kg body weight). We systematically evaluated its developmental immunotoxicity through three integrated dimensions: 1) immune organs (thymus, spleen), 2) intestinal barrier integrity (duodenum), 3) innate immune cells (natural killer cells, myeloid cells) and adaptive immune components (T/B lymphocyte subsets), combined with cytokine network profiling and immunoglobulin quantification. The results demonstrated that T-2 toxin induced thymic cortical atrophy, structural damage to splenic corpuscles, and mesenteric lymph node disorganization with hemorrhagic foci. It significantly inhibited NK cell cytotoxic activity (p < 0.001), dose-dependently reduced the proportions of CD3+ , CD3+CD4+, CD3+CD8+, regulatory T (Treg) cells, and B lymphocyte subsets, and decreased the CD4+/CD8+ ratio (all p < 0.001). Furthermore, serum levels of IgA, IgG, and IgM were significantly reduced (p < 0.001), while immune damage was exacerbated by disrupted cytokine secretion and apoptosis induction. This study demonstrates that T-2 toxin induces systemic immune deficiency during development through structural disruption of immune organs, suppression of both innate and adaptive immune functions, and induction of immune cell apoptosis. The study demonstrates that T-2 toxin induces systemic immune deficiency during development by disrupting immune organ structure, suppressing both innate and adaptive immune functions, and promoting immune cell apoptosis. For the first time, this study highlights the heightened sensitivity of the developing immune system to T-2 toxin, providing a theoretical foundation for the prevention and control of mycotoxin-induced developmental immune deficiency.